A resistência na Assembleia Legislativa de São Paulo: como atuaram os deputados estaduais que combateram a ditadura militar - Cezarino, Viviane Oranges (2018)
This study analyzes how the opposition composed by state representatives of the MDB (Brazilian Democratic Movement) acted in the Legislative Assembly of São Paulo during military dictatorship. The objective is to describe the strategies developed by the members of the MDB to difficult the work of the people at ARENA´S (National Renewal Alliance) party. The focus is to address the opposition's actions when it was a minority in the State Parliament (they were 15 representatives of MDB against 51 ones of ARENA). And subsequently, from 1975 onwards when it became majority. Opposition used regimental instruments, such as speeches, to disturb military dictatorship and report disappearances and deaths. In addition it found gaps that made ALESP an "island of freedom" in such dark times. Sixteen ex-state representatives from MDB provided information to this monograph elaboration. These were testimonies and reports i listened to during the recordings of the documentary show "Memories of Legislative Power", from SP Assembly TV. The trajectories that these men have created to reach State Parliament of Sao Paulo point to fight ideals and political participation. Together, these aspects contributed to São Paulo Legislative Assembly in becoming a stone in the middle of the general's road